Thinking about transformations in space and identity: American frontiers, old and new - Salim KERBOUA (Akofena, 2023)
Abstract: Space has always played a significant role in the identity formation of human groupings. The sense of belonging is not only historical and social but also spatial. Space gives meaning to identity as much as identity seeks specific spaces in which it can subsist and thrive. The present paper analyses the symbiotic relationship between space and identity in the United States' historical and cultural imagination. The article probes how the dynamic transformation and appropriation of spaces have been central elements in the inception, development and expansion of the American collective character. The article attempts to apprehend the American self-proclaimed idea of the United States as an exceptional and ever-expanding entity, and it examines how character and identity have attempted to define the appropriation and control of territorialized and de-territorialized spaces. But more importantly, the article argues that space has had changing meanings and has taken different manifestations in US cultural, social, and political history.